Aluminum hydroxide colloid vaccine encapsulated in yeast shells with enhanced humoral and cellular immune responses. (June 2018) - Liu, Hui; Jia, Zhenghu; Yang, Chengmao; Song, Mei; Jing, Zhe; Zhao, Yapu; Wu, Zhenzhou; Zhao, Liqing; Wei, Dongsheng; Yin, Zhinan; Hong, Zhangyong
Abstract: Aluminum salt (Alum) is one of the most important immune adjuvants approved for use in humans, however it is not suitable for vaccination against various chronic infectious diseases and cancers for not being able to induce cell-mediated (Th1) immunity. Here, we encapsulated an Alum colloid inside β- glucan particles (GPs), which are a type of natural particles derived from the yeast glucan shells, to prepare hybrid GP-Alum (GP-Al) adjuvant particles with a very uniform size of 2–4 μm. These hybrid particles can be used to load antigen proteins through a simple mixing procedure, and can be highly specifically targeted to antigen-presenting cells (APCs) and strongly activate dendritic cells (DCs) maturation and cytokine secretion. In an animal model, they elicit a strong Th1-biased immune response and extremely high antibody titer, and cause marked prophylactic and therapeutic effects against tumors. As Alum has been proven to be a safe adjuvant to induce strong humoral responses and β-glucans are safe for human use, this very uniform hybrid Alum particulate system could have important application as a vaccine carrier to stimulate humoral and cellular immune responses at the same time. Graphical abstract: